Analysis performance of content delivery network by used Rateless Code method - Sitorus, Sahat Parulian; Hasibuan, Elysa Rohayani; Rohani, Rohani (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Content Delivery Network (CDN) is a server system network to content contribution in an application/web to various accessors around the world so that data sent and received by users was faster. Server selection algorithm determines the extent to which the quality of server service to client requests. This study to analyze  CDN performance, used Geographical algorithm Domain Name Server (GeoDNS), Round Robin (RR), Weigthed Round Robin (WRR), dan Least Connection (LC). In addition, Rateless Code (RLC) is also applied to reduce packet loss, there are two methods used, namely the first method is rateless code 50 and the second method is rateless code 100. Thus, the trial was carried out 20 times. Besides that, it is also applied Rateless Code (RLC) to less packet loss. From the research results, the use of CDN can improve server service performance. CDN managed to reduce the maximum to the average delay about 67,6%. From the studied CDN algorithm, Geo DNS experienced the lowest delay up to about 67.6 ms, however LC experienced the lowest packet loss, namely about 2,84%. The application of rateless code on CDN with LC algorithm succeeded in reducing packet loss to about 2.84%, but delay increased to about 75.3%.